Natural Occurrence Of Aschersonia Aleyrodis On Citrus Black Fly In Vidarbha Region Of Maharashtra (Journal of Plant Disease Sciences, 2019)
Mandarin orange (Citrus reticulata) is most common among citrus fruits grown in Vidarbha region of Maharashtra. It occupies nearly over 1.30 lakh hectares area in Vidarbha. In Vidarbha region mandarin production is concentrated in Nagpur, Amravati and Akola district.As citrus is being widely grown across the region, its cultivation faces variety of problems. The major problem includes threat of insect pests, diseases and nutrient deficiencies. Among the problems responsible for low production and low fruits quality, insect pests are of major concern.In Maharashtra state, 14 species were reported of which 8 species are of significant importance (Thakare, et al., 1985 and Anonymous, 1994). Major insect pests of citrus include White fly, Black fly, Citrus psylla, Lemon butterfly, Leaf miner, Fruit sucking moth etc.These insect species also exist on citrus in Vidarbha and cause serious damage (Anonymous, 1995). In a comprehensive review estimated loss of about 30 per cent of citrus group due to damage caused by insect pests has been reported (Bindra, 1967).
Keywords: Aschersonia aleprodis; Black fly; Citrus; Characters